ANALISIS PERSEPSI EMPLOYEE EMPOWERMENT TERHADAP TURNOVER INTENTION KARYAWAN PADA HOTEL RATU MAYANG GARDEN PEKANBARU - Muhajir Mabruri; Marzolina '; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted on employees Ratu Mayang Garden Hotel Pekanbaru. Aims to determine the effect of simultaneous and partial perception of the Employee Empowerment Employee Turnover Intention at Ratu Mayang Garden Hotel Pekanbaru. There are five variables, one dependent variable and four independent variables. The study was conducted with a sample of 98 people. Research using test equipment and multiple regression analysis using census techniques by giving questionnaires to the respondents. In terms of data analysis,using qualitative and quantitative methods using SPSS (Statistical Package for Social Sciences) version 20.0. The analysis showed that there are significant variables simultaneously and partially Meaningfullness, Competence Self-Determination and Impact on Employee Turnover Intention at Ratu Mayang Garden Hotel Pekanbaru. The variables that most strongly to Employee Turnover Intention at Ratu Mayang Garden Hotel Pekanbaru is variable Self-Determination (X3) when all employees are good Employee Empowerment is good, it will be able to lower the Employee Turnover Intention at Ratu MayangGarden Hotel Pekanbaru. Keywords: Meaningfullness, Competence, Self-Determination, Impact, and Turnover Intention